Hammerhead ribozymes directed against mRNA of an essential gene inhibit Escherichia coli growth and enhance tetracycline efficacy - Miszkiewicz-Golec, Joanna; Maximowa, Ksenia; Łukaszewicz, Maciej; Bartosik, Dariusz; Darżynkiewicz, Edward; Trylska, Joanna (Frontiers in Microbiology, 2025)
Aiming to find novel ways to inhibit bacterial growth, we tested hammerhead ribozymes targeting the mRNAacpP transcript, which encodes the essential acyl carrier protein in Escherichia coli. We engineered ribozymes with varying catalytic cores and arm lengths, finding that while short-armed ribozymes showed higher activity in vitro, long-armed variants demonstrated superior growth inhibition in vivo. Isothermal titration calorimetry confirmed tight binding between the ribozymes and the mRNA substrate, with association constants between 107 and 108 M−1, and gel electrophoresis verified substrate cleavage. Ribozymes were incorporated into bacterial plasmids, introduced via transformation into E. coli, and were expressed in a controlled manner, inhibiting bacterial growth by up to 70% over 24 h. Notably, ribozymes embedded within tRNA structures, a strategy intended to protect them from intracellular degradation, showed differential effectiveness compared to standalone variants; tRNA scaffolding preserved activity in long-armed but abolished it in short-armed constructs. Growth inhibition resulted from both mRNA cleavage and translational blocking, as demonstrated by comparing active ribozymes with their catalytically inactive variants. Furthermore, tetracycline efficacy was enhanced 2- to 4-fold in cells expressing ribozymes, indicating potential for synergy. This study demonstrates the first successful targeting of an essential gene in E. coli using hammerhead ribozymes, achieving growth inhibition through combined mechanisms of mRNA blocking and cleavage, and highlighting the potential of ribozymes as antibacterial strategies.